Instrument for evaluating digital educational comic - Zaibon, Syamsul Bahrin; Azman, Farah Nadia; Shiratuddin, Norshuhada (2019)
Digital educational comic allows learners’ knowledge and ideas on various subjects to be synthesized in a form of digital comic. Digital educational comic not only contains informative and emotive elements, but also engages the learners emotionally. In order to know the digital educational comic is valuable to leaners, it is needed to be evaluated properly. In specific, it should be measured based on what level it is able to educate and entertain the leaners. However, to date the standard evaluation of digital educational comic is scarce. Therefore, this paper aims to present the design, development, and validation of an instrument for evaluating digital educational comic. The instrument focuses on evaluating two main aspects of the digital educational comic: learning (12 items) and entertainment (8 items) which were based on the literature of comic core elements. Content validity, face validity, and reliability tests were carried out and the instrument shows satisfactory properties and could be useful in the educational environment and research. The use of the instrument may contribute to a deeper understanding of digital educational comic properties, valuable for comic development and improvements of quality in comic educational content.